Psychological First Aid For Disaster Preparedness Student Organization Members - Vera Nova; Iyulen Pebry Zuanny; Karjuniwati Karjuniwati; Rahil Naila (Psikoislamedia : Jurnal Psikologi, 2024)
Aceh is one of the provinces in Indonesia that is prone to disasters. Facing these conditions, there is a need for disaster preparedness, especially for student organization members who are agents of change. Improving disaster preparedness requires knowledge of providing psychological assistance during and after disasters. This study aims to see the effect of Psychological First Aid knowledge on the disaster preparedness of student organization members at UIN Ar-Raniry Banda Aceh. This research used a quantitative approach with regression analysis as the main method and descriptive analysis as a supporting method. The participants in this study were 37 student organization members spread across several faculties at UIN Ar-Raniry. The results showed that there was an influence of Psychological First Aid (PFA) knowledge on the disaster preparedness of student organization members at UIN Ar-Raniry Banda with a value of β=0.864, ρ=0.000 (ρ<0.05). This research has implications for improving student organization member's knowledge and preparedness in facing disaster.